P36 Applying the Baveno criteira on patients with compensated liver cirrhosis: tertiary liver unit audit. (20th September 2022) - Avades, Tamar; Wood, Callum; Jiju, Prince; Barstow, Jack
Abstract : Introduction: The current Baveno VI criteria dictate that cirrhotic patients with a liver stiffness (LF) of less than 20kPa and a platelet count of >150x10^9 are low risk of developing oesophageal varices (OV). Patients with compensated cirrhosis criteria are surveyed every 2–3 years if there is no evidence of OV, or every year if there is evidence of OV. Our aim was to establish whether a tertiary liver unit was appropriately referring patients for an OGD. Method: We collected the following data from patients with a diagnosis of compensated liver cirrhosis: LF, platelet count, aeitology of liver disease, and results of an index OGD. Data was obtained from 300 patients. The aeitology of liver cirrhosis was as follows: ARLD (49%), NAFLD (19%), ASH+NASH (5%), viral hepatitis (15%), autoimmune (6%), cryptogenic (3%), and unknown/other (3%). Results: 204 patients (68%) were referred for a fibroscan. Of those, 113 (55%) had a LF of more than 20 kPA, and 86 patients (76%) were referred for an OGD. The findings of the endoscopy are shown in figure 1 . 60% of patients had evidence of OV on their index scope. 182 of 300 patients (60%) had platelets <150x10^9, and 149 (82%) were referred for an OGD. The findings of the OGD are shown in figure 2 . 60% had evidence of OV on their index scope. 53 patients (18%) had both normal LF and platelet count. Despite this, 25 (47%) were referred for an index OGD for OV surveillance. 22 patients (88%) had a normal examination, and 12% had evidence of OV (see figure 3 ). 76 patients (25%) had both abnormal LF and platelet count, and 58 (76%) were referred for an index scope. Varices were present in 55% of these cases. There were no risks identified in those not referred for an OGD, when it was clinically indicated. Discussion: We found that patients with abnormalities in LF and/or platelet count were referred for an index OGD in more than 70% of cases. The presence of OV was identified in 55–60% of cases. 24% of patients with abnormalities in both LF and platelet count were not referred for an OGD. Conversely, despite not meeting Baveno criteria, 18% of patients were referred for an OGD, which was normal in 88%. With current unavoidable delays with surveillance endoscopy, applying the Baveno criteria can avoid unnecessary invasive procedures.